Comparative analysis of microbial composition and functional characteristics in dental plaque and saliva of oral cancer patients - Man Zhang; Yiming Zhao; Abdulrahim Umar; Hailin Zhang; Lirong Yang; Jing Huang; Ying Long; Zheng Yu (BMC, 2024)
Abstract Background The oral cavity is home to various ecological niches, each with its own unique microbial composition. Understanding the microbial communities and gene composition in different ecological niches within the oral cavity of oral cancer (OC) patients is crucial for determining how these microbial populations contribute to disease progression. Methods In this study, saliva and dental plaque samples were collected from patients with OC. Metagenomic sequencing was employed to analyze the microbial community classification and functional composition of the different sample groups. Results The results of the study revealed significant differences in both the function and classification of microbial communities between saliva and dental plaque samples. The diversity of microbial species in saliva was found to be higher compared to  that in plaque samples. Notably, Actinobacteria were enriched in the dental plaque of OC patients. Furthermore, the study identified several inter-group differential marker species, including Prevotella intermedia, Haemophilus parahaemolyticus, Actinomyces radius, Corynebacterium matruchitii, and Veillonella atypica. Additionally, 1,353 differential genes were annotated into 23 functional pathways. Interestingly, a significant correlation was observed between differentially labeled species and Herpes simplex virus 1 (HSV-1) infection, which may be related to the occurrence and development of cancer. Conclusions Significant differences in the microbial and genetic composition of saliva and dental plaque samples were observed in OC patients. Furthermore, pathogenic bacteria associated with oral diseases were predominantly enriched in saliva. The identification of inter-group differential biomarkers and pathways provide insights into the relationship between oral microbiota and the occurrence and development of OC.